Sense Of Place On Tourist Attractions In Central Aceh Regency - Rinaldi Mirsa; Muhammad Muhammad; Eri Saputra; Ayike Kusprasetya; Rizki Alamsyah (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
Sense of place is related to the relationship between human reactions and space that affects expression and emotion in response to environmental conditions in a place. Takengon City has many tourist destinations, including the Al-Kahfi Pantan Terong Peak tour, Batu Susun tourism, and Bebalen Cafe Pantan Terong which support a wealth of natural potential and is the main attraction for tourist visitors located in the Ulu Nuih Village area, Bebesen District. The purpose of this research is to examine the sense of place in the Ulu Nuih Village Tourism area, Bebesan District through the elements that form the place, namely visual characters, activity, and images. Then find out the level of sense of place contained in each tour and what elements are the strongest in the tourist area. The research uses the Behavioral Mapping method to describe the behavior in the map, behavior, and shows the relationship between the behavior and a specific design and also uses quantitative methods to collect data using research instruments, quantitative/statistical data analysis is used to examine a sample. The concept is described in the variables of its constituent elements. The results showed that the thing that most influenced the sense of place was Landmark a marker of tourist sites, sequences, and satisfaction with the overall building arrangement of the tour that was neatly arranged, and organized the environment was maintained. Satisfaction with tourists was an influential variable in tourism in Ulu Nuih Village, Bebesen District. While the thing that is at the lowest level is resilience where most of the visitors are only present to capture the moment and then leave the tourist location.